Program “SUPER” untuk Meningkatkan Komitmen Perkawinan - Alfi Fatima Yudani; Tina Afiatin (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2018)
Low marital commitments can cause many marital problems. Therefore, interventions that can increase marriage commitments are needed. This study aims to determine the effect of the "SUPER" Program in increasing marital commitment. The "SUPER" program is an intervention based on the techniques of creating gratitude according to the stages in the experiential learning cycle and implemented in four sessions. This quasi-experimental study was conducted with untreated control group design with pretest and posttest in 12 women who have been married for 1 to 10 years. The result of the difference of gained score analysis in the experimental group and control group with Mann-Whitney U test showed Z score = -2.089 p = 0,037 (p <0,05). The Wilcoxon Signed-Rank Test was performed on the experimental group showed Z score = -1,997 p = 0.046 (p <0.05). The results showed that there were significant differences between the experimental group compared with the control group. There was a significant increase in the marital commitment score between the pretest and posttest experimental groups